THE THEMATIC RELATION OF THE SUBJECTS IN THE “SNOW WHITE AND THE HUNTSMAN” MOVIE SCRIPT: A SYNTACTICAL ANALYSIS - Noor Vatha Nabilla; Miftahul Huda (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Every language in the world has their own characteristic of syntactical structure. The important parts in grammatical system include subject, direct object, and indirect object (Van Valin, 2004). This study aims to find out the thematic relation of the subjects in the movie script. The data source of the study was taken from “Snow White and The Huntsman” movie script. The data used the clauses available in the script that contained verb-specific semantic role to identify whether the subject was categorized as agent, experiencer, recipient, stimulus, theme, or patient. The data were analyzed by using thematic relation categorization proposed by Van Valin (2004). The result showed that there are five semantic roles of subjects found in the script such as agent, experiencer, recipient, theme, and patient. The finding seems to contribute filling the gaps of the previous studies as well as providing a gap for further inquiries to be explored more by the future researchers.